The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.foodchem.2018.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritional characterization of Chenopodium quinoa Willd (quinoa) grains: A good alternative to nutritious food

Abstract: With the purpose of valuing the species Chenopodium quinoa Willd (quinoa), as well as encouraging the consumption of its grains, this study aimed at providing a detailed evaluation of the nutritional value and chemical composition of several quinoa grains of different colour varieties (black, red and white) from different origins. The results demonstrated an excellent composition, namely in the presence of many compounds of interest, such as organic acids, tocopherols and unsaturated fatty acids, as well as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 24 publications
(36 reference statements)
10
141
3
10
Order By: Relevance
“…in Rainbow, with an average content of 37.6 g kg −1 d.m. These values were comparable with other data presented in the literature …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…in Rainbow, with an average content of 37.6 g kg −1 d.m. These values were comparable with other data presented in the literature …”
Section: Resultssupporting
confidence: 93%
“…(Table ), which was higher than the fat content in corn, wheat, or rice grains, and comparable to that in oats . Similar amounts of fat were reported by Pereira et al ., while Bhargava et al . found that the lipid content in quinoa ranged from 18 to 95 g kg −1 .…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations